2004
DOI: 10.1038/labinvest.3700055
|View full text |Cite
|
Sign up to set email alerts
|

Immune system and prognosis in colorectal cancer: a detailed immunohistochemical analysis

Abstract: The efficacy of tumor cell-immune cell interactions depends on a number of factors, for example, the expression of HLA-I on tumor cells, the type of immune cell, the accessibility of tumor cells for immune cells and the expression of immunogenic epitopes. We assessed infiltration of CD4 þ , CD8 þ , CD56 þ and CD57 þ cells in the tumor epithelium, tumor stroma and advancing tumor margin of 93 colorectal carcinomas and correlated this to clinicopathological parameters, the expression of HLA-A and HLA-B/C on tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
172
3
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(186 citation statements)
references
References 33 publications
10
172
3
1
Order By: Relevance
“…58 T-cell infiltration is not homogeneous in colorectal cancer, and attention has therefore also been focused on the predictive values of T cells in different tumor compartments. 32,33,37,[42][43][44][45][46][47] In this study, the separate measurements of T-cell infiltration in the tumor front, center, and intraepithelial compartment were closely correlated and were all positively associated with cancer-specific survival. Two previous studies found that a high total lymphocyte score, similar to that used in this study, more accurately predicted cancer-specific survival compared with any single score separately.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…58 T-cell infiltration is not homogeneous in colorectal cancer, and attention has therefore also been focused on the predictive values of T cells in different tumor compartments. 32,33,37,[42][43][44][45][46][47] In this study, the separate measurements of T-cell infiltration in the tumor front, center, and intraepithelial compartment were closely correlated and were all positively associated with cancer-specific survival. Two previous studies found that a high total lymphocyte score, similar to that used in this study, more accurately predicted cancer-specific survival compared with any single score separately.…”
Section: Discussionmentioning
confidence: 95%
“…[24][25][26][27][28][29][30][31][32][33] As in this study, MSI tumors have previously been reported to have a higher degree of T-cell infiltration than MSS tumors. [35][36][37] Yet the potential confounding effect of MSI screening status on the prognostic importance of T-cell infiltration has been considered in only a minority of reports, of which most, 32,36,[39][40][41]46,53,54 but not all, 30,55 found that the better prognosis associated with dense T-cell infiltration was independent of MSI screening status. In this study, a better prognosis was seen in patients with MSS tumors densely infiltrated by T cells compared with poorly or intermediately infiltrated MSI tumors, whereas MSI screening status was not significantly related to prognosis in subgroups of highly and poorly infiltrated tumors separately.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using IHC techniques, Menon et al 9 analyzed resected colorectal cancer samples from 93 patients with stage II/III colon cancer, and found that both higher CD 8 C (P D 0.04) and CD 57C (P D 0.05) cell infiltration within the tumor margin correlated with prolonged disease free survival in multivariate analysis. After an immunohistochemical analysis of 843 colorectal cancer specimens, Ogino et al 10 found that intra-tumor as well as peri-tumor lymphocytic infiltration were both associated with longer OS (P D 0.005 and P D 0.014 respectively).…”
Section: Evaluating Immune Responses After Sipuleucel-t Therapymentioning
confidence: 99%